Faktor Yang Berhubungan Dengan Pemberian Imunisasi Dasar Lengkap Pada Anak Usia 1-2 Tahun Di Wilayah Kerja Puskesmas Kopelma Darussalam - Mauliza, Riska; Fitria , Fitria; Riza , Nelva; Riansyah, Ferdi (Teewan Solutions, 2024)
In Indonesia , there are still many health problems , especially in the field of complete basic immunization, which should be prevented by providing complete basic immunization. If this infectious disease is not immediately prevented by giving complete basic immunizations to children, it will cause pain, disability, and even death to the sufferer. The purpose of the study is to find out the factors related to the provision of complete basic immunization at the age of 1-2 years in the working area of the Kopelma Darussalam Health Center . The research method is a Cross Sectional approach . The population in this study is all mothers who have children aged 1-2 years in the Kopelma Darussalam Health Center Working Area, which totals 217 people. Sampling in this study used a stratified random sampling technique of 68 respondents. This research has been carried out from July 10 to August 31, 2024 by distributing questionnaires. Data processing is carried out using SPSS. The results of this study were analyzed using univariate and bivariate analysis .The results of univariate analysis showed that the majority of children in the 1-year category were 45 children (66.2%), that the majority of maternal education in the primary education category was 41 mothers (60.3%), the majority of mothers in the non-working category were 59 mothers (86.8%), the majority of children with incomplete basic immunization were 45 children (66.2%), the results of the bivariate analysis showed the results of the P-value value 0.000 (<0.05) This shows that there is a relationship between maternal knowledge and the administration of basic immunization in children, a P-value of 0.013 (<0.05) was obtained, this means that there is a relationship between family support and the provision of basic immunization to children. It is recommended to mothers to increase their knowledge about health by providing complete basic immunizations to children.